Phytase Producing Fungi and Their Efficiency in Hydrolyzing Phytin-P Compounds - Yadva, B K; Tarafdar, J C; Panwar, J; Yadav, R S (Annals of Arid Zone, 2016)
Five most efficient phytase producing fungi belonging to genus Aspergillus, Emericella, Gliocladium, Penicillium and Trichoderma were isolated from arid and semi-arid soils and tested for their efficiency in hydrolyzing phytin-P compounds. Penicilliul11 purpurogellul11 accumulated more biomass closely followed by Trichoderma harzianum during the growth period. A strong negative correlation (r = - 0.91, n = 20, P <0.01) was observed between development of fungal mat and pH of the media. The extracellular phytase released by the organisms was 12.7 times more than their intracellular phytase. The extracellular phytase activity was more in Emericella rugulosa, whereas intracellular phytase activity was more in Trichoderma harziallu11l. Emericella rugulosa was found to be the most efficient in hydrolyzing phytin-P (98.82J..lgg-l). The results indicated that Emericella rugulosa can be used as a biofertilizer under arid and semi-arid environments for native P mobilization. Key words: Fungi, efficiency, phytase, phytin-P, hydrolysis.